Mean high-dose l-Thyroxine treatment is efficient and safe to achieve a normal IQ in young adult patients with congenital Hypothyroidism - Aleksander, Paulina; Brückner-Spieler, Michaela; Stoehr, Anne-Marie; Lankes, Erwin; Kühnen, Peter; Schnabel, Dirk; Ernert, Andrea; Stäblein, Walter; Craig, Maria E.; Blankenstein, Oliver; Grüters-Kieslich, Annette; Krude, Heiko (The journal of clinical endocrinology & metabolism, 2018)
Patients with congenital hypothyroidism treated early with high-dose l-thyroxine had normal psychomotor, metabolic, and quality of life outcomes in young adulth
Gesehen am 04.05.2020